Lacrimal Location of Sinus Histiocytosis (Destombes-Rosai-Dorfman Disease) - Azoulay, Robin; Brisse, Hervé; Fréneaux, Paul; Ferey, Solène; Kalifa, Gabriel; Adamsbaum, Catherine (American Journal of Neuroradiology, 2004)
Summary: A 7-year-old West African male patient presented with recurrence of multiple cervical lymphadenopathy. Cervical node biopsy disclosed a sinus histiocytosis with massive lymphadenopathy (Rosai-Dorfman-Destombes disease). During follow-up, the patient developed a left orbital mass corresponding to an enlarged lacrimal gland shown by CT. The histologic features of the gland were consistent with the diagnosis, and with steroid treatment, the gland decreased in size. Although rare, the diagnosis of sinus histiocytosis with massive lymphadenopathy has to be considered in cases of lacrimal gland enlargement.